A comparative life cycle assessment of dry and wet anaerobic digestion technologies for food waste management - Rozieana Abu,; Muhammad Arif Ab Aziz,; Zainura Zainon Noor,; Rohaya Abd Jalil, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Anaerobic digestion (AD) is especially useful in the treatment of organic waste sources, such as food waste (FW) since AD can support the generation of clean energy while preventing the hazards of uncontrolled GHG pollution originating from landfills. However, the potential environmental impacts of dry AD and integrated wet AD treatment are largely unknown, particularly in Malaysia. Thus, this study aimed to compare the potential environmental impacts of four FW treatment technologies in Malaysia: landfill (Sc0), dry anaerobic digestion (Sc1), wet anaerobic digestion combined with windrow composting (Sc2), and wet anaerobic digestion combined with windrow composting and landfill (Sc3). The scenario modelling was performed via GaBi v6.0 software using 1 ton of pre-treated FW as a functional unit, with the analysis of environmental impact scores being based on the ReCiPe (H) v1.07 characterization method. At the midpoint assessment, the Sc1 produced extensive improvements in 12 mid-point impact categories, being the most environmentally favoured FW treatment method compared to the other options in critical categories such as global warming, depletion of fossils and agricultural land occupation. The Sc1 mesophilic conducting reactor in this study used less energy for heating, without generating waste water while requiring a small operating area. Sc3 had the lowest environmental performance since the emissions into the air from windrow composting and landfill were discharged completely without any form of treatment like capturing or flaring. Finally, through the single score analysis, Sc1 was regarded as an appropriate FW treatment technology with the least damaging impact on resource depletion, human health, and ecosystems in comparison to all scenarios. This was accomplished through relatively low power demands for the operation, shorter road transport distances, and a substantial reduction in the amount of waste and electricity generation. These analyses provide a useful framework for understanding the important characteristics of anaerobic treatment despite the divergent challenges faced by the different processes.